MELOMICS: Contributions of computer science and biology to receptive music therapy - Vico-Vela, Francisco José; Sánchez-Quintana, Carlos Alberto; Albarracín Molina, David Daniel (My University, 2014)
It is surprising the fact that while the personalized medicine model is more and more accepted, receptive music therapy is still applied collectively. Although, in some hospitals the subject (patient or health-medical staff) is allowed to select the genre or artist, with most published clinical studies reporting on concrete types of music (eg, relaxing or classical) that are applied to groups of patients. Customizing songs to patient characteristics would make the study much more complex: on the one hand, a higher variability demands a larger sample and, on the other hand, it significantly increases the time and care dedicated to each patient. In any case, customization is a subjective element which strongly depends on individual preferences. MELOMICS integrates computer technology that adapts music to the condition of the patient, in an automatic and objective way. This enables the future design of biofeedback devices, which in the long run results in being favorable for the therapeutic response of the patient.
Keywords: Musicoterapia; Aplicaciones informáticas; Receptive music therapy; Generative music; Biofeedback